Collective Efforts for the Conservation of Sea Turtles in the Gulf of California - Tiburcio Pintos, Graciela (2017)
This article is about the history of some outstanding characters and groups dedicated to the conservation of the five species of marine turtles known for the Gulf of California, they are today a regional symbol of conservation. These efforts are processes shared by diverse actors and are generally promoted by students and scientists, supported by coastal fisherfolk. Civil associations, environmental authorities and entrepreneurs later become incorporated. All of them take support from the legislation established after intensive exploitation between 1960 and 1970, in order to avoid the extinction of these species. This history of collective efforts shows that the success of conservation is grounded in synergies among actors and in the convergence of top-down and bottom-up processes.